Pengaruh Permainan Tradisional Terhadap Kerja Sama Siswa Dalam Pendidikan Jasmani di SMP Islam Bani Ahmad Cilamaya - Rizky Maulana; Muhammad Mury Syafei; Citra Resita (Jurnal Literasi Olahraga, 2021)
The aim of this research is to determine, analyze and identify the effect of traditional games for students’ cooperation in physical education learning at junior high school bani ahmad islamic cilamaya. To answer the problem formulation that has been proposed , the researcher uses a approach quantitative with experimental method. This research is conducted in junior high school Islam Bani Ahmad Cilamaya by taking two classes as samples of this research , the 8th grade A with 26 students as a experiment class, and the 8th grade B with 26 students as control class of the total 52 in 8th grade. This research was divided into three stages, namely pretest , treatment and posttest. The pretest conducted in both grade samples to determine the ability or the early results of student’s cooperation before taking the reatment. After pretest, researcher provide treatment as much as eight meetings in experiment class and control class both by the teacher and the researcher, in experiment class using traditional games while in control class using conventional the learning. After the treatment was given, the researcher then conducted a posttest in the experimental class and the control class . Is there any effect of student cooperation after using traditional game learning in the experimental class . Then the Analysis of Covariance (ANCOVA) was used to analyze the data. After the research is done and the results have been analyzed to prove that the traditional game in teaching physical education give an effect to students’ cooperation with following explaination : 1) The application of traditional game in teaching physical education give effect to students’ cooperation. 2) The application of the conventional model in teaching physical education take effect on the students’ cooperation. 3) Application of traditional game more significant effect of the conventional model in teaching physical education to students’ cooperation.